Transformasi Digital dan Dampak PHK Indosat: Analisis Determinasi Teknologi Berdasarkan Teori McLuhan - Dedy Putra Widi Utama; Ana Kuswanti; Munadhil Abdul Muqsith (Universitas Islam Raden Rahmat, Malang, 2024)
This study integrates technology and communication science perspectives, focusing on the impact of digital transformation on layoffs at Indosat in February 2020. The research aims to analyze the relationship between the adoption of new technology and layoffs using Marshall McLuhan's theory. The study employs qualitative methods through in-depth interviews with 10 affected former employees. The findings reveal that digital transformation and automation enhance operational efficiency but cause significant changes in workforce structure and internal dynamics. Former employees associate layoffs with downsizing strategies that impact their well-being. The study explains that communication technology successfully shapes organizational culture and social interactions. In conclusion, it is essential for companies to develop comprehensive change management strategies that consider employee well-being alongside operational efficiency to balance business goals with social responsibility and ensure organizational sustainability.